The psychology of gifted children : perspectives on development and education - Freeman, Joan (John Wiley and Sons, 1985)
This book provides an overview of current international understanding of the psychology of gifted children. The psychological and social development of very able children is considered within the wider context of more general processes of child development. The contributions, which review and report both research findings and personal experiences, are all original, particular emphasis being placed on their practical implications. The three major overlapping concerns of the book are in sections: the first tackles the problems of definition and identification of the gifted, especially those who do not show their gifts; the second focuses on how it is to be gifted, on the characteristics and behaviour of the children; and in the third section, consideration and suggestions are given about their education.